PENERAPAN SENI LUKIS DEKORATIF PADA KERAMIK TABLEWARE - Halim, Ivana Gabriella; Mustika, I Ketut; Yudha, I Made Bendi (Program Studi Seni Murni ISI Bali, 2025)
This internship/work practice report explores the theme of nature and its surroundings as the inspiration for creating artwork. In this project, the author is inspired by the natural environment, including the sea, leaves, and stones. From these ideas, textures, shapes, and colors are developed in the artworks. The work created will be tableware. Tableware refers to the dishes and utensils used by people for eating and drinking. Besides its primary functions of eating, serving food, and setting the table, tableware can also serve as decorative art that can be displayed. The goal of this project is to make functional tableware more attractive by applying painting art, making it not only functional but also decorative. The artworks feature various techniques in terms of shape, texture, coloring, decoration, and more. The creation process begins with observation, studying, and managing ideas, followed by contemplation, and ultimately the creative process is realized through painting on ceramics. This report aims to understand the utility of the tools and materials, as well as the stages of the creation process. In conclusion, the author has gained valuable learning and knowledge during the internship/work practice. The author hopes that this creation will serve as an inspirational piece for readers.